Sustainable Livestock Farming for Improving Socio-Economic Condition - Mohammad Shamsuddoha; Mohammed Quaddus; Desmond Klass (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2013)
Sustainability is the most effective concept to improve socio-economic condition, including environment. Constructive socio-economic changes are getting priority in recent years among academia and business sector in Bangladesh. Bangladesh poultry sub-sector has long supply chains having associated with various stakeholders. In this paper, a case poultry farm was taken to examine a production process that links with socio-economic benefits. Design science method under the quantitative paradigm was chosen to develop a model for the case industry. A Simulation model was developed using simul8 software to construct the real poultry operation. The objectives of this paper are to construct a sustainable model for a case poultry industry along with socio-economic issues. Later, simulated model output will examine it through various performance indicators (KPIs) to find out the impacts on socio-economic benefits. Numbers of KPIs have been briefly discussed in light of the research problem to illustrate positive effects of sustainable production.